Mapping of Artificial Intelligence and Robotics Technologies Applied to Offshore Wind Energy - Pussaignolli de Paula, Matheus; Noronha, Matheus; Garcia Valente, Uiara; Inacio Domingues, Beatriz Regina; Jahn Souza , Letícia (Journal of Sustainable Competitive Intelligence, 2024)
Objective: this paper aims to map the main artificial intelligence and robotics technologies that are being applied in offshore wind farms around the world, as well as highlight the possible classification of these technologies in Brazil. Methodology/approach: the methodology of the work consists of carrying out a bibliometric study based on a Scopus database where a series of quantitative and qualitative analyses were made and, finally, the main papers were grouped into 8 central clusters found. Originality/Relevance: The relevance of the work consists of presenting to researchers the main fields that have been studied in the applications of AI and robotics in the context of offshore wind farms and, therefore, allows new research to occur in these fields found from the clusters. In addition, the work summarizes in which stages throughout the development of offshore projects each of the clusters can be applied, thus allowing a significant advance for possible projects to be carried out in Brazil in the future. Main conclusions: as a result of the research, eight main clusters of research carried out in the field were identified, as well as their possible classification in the Brazilian scenario in the future. Theoretical/methodological contributions: the scientific contributions that the paper presents to researchers are diverse, among which we can list: the mapping of the main journals that have publications on the theme of AI and robotics applications in the field of offshore wind energy, the main trends in AI and robotics technologies applied to offshore wind energy around the world and, finally, the mapping of the most relevant paper on AI and robotics applications in the context of offshore wind energy, as well as their evidence in the Brazilian context.